Anatomical and morphological characteristics of beech wood after CO2-laser cutting. Issue 6 (2nd November 2022) - Rezaei, Fatemeh; Wimmer, Rupert; Gaff, Milan; Gusenbauer, Claudia; Frömel-Frybort, Stephan; Kumar Sethy, Anil; Corleto, Roberto; Ditommaso, Gianluca; Niemz, Peter
ABSTRACT: This study aimed to characterize the surface quality of beech wood ( Fagus sylvatica L . ) cut by a CO2 -laser. Boards were conditioned to a low (about 8% moisture content), 12% and a high, (about 18% moisture content). Laser cutting was performed at varying processing parameters, i.e. cutting speed, gas pressure and focal-point position. A confocal microscope was used to determine the average surface roughness perpendicular to the grain. The anatomical structures of the laser-cut surfaces were examined with scanning electron microscope. The result showed that smoother surfaces were obtained at the low moisture content when processed at a gas pressure of 21 bar. Focal-point positioning did only have an effect on the surface roughness at 12% moisture content whereas the value was substantially lower for focal-point positioned on the surface. The surfaces cut at 18% moisture content, and at a cutting speed of 3.5 m/min generated a rougher surface than cut at low moisture content and at a lower speed. Laser cutting produced a rougher surface as compared to sawn surface (circular saw). The structural integrity of the laser-cut surface was more intact when the wood was having high moisture content and processed at a high cutting speed.